Logično mehko krmiljenje aktivnega vzmetenja brez upada njegove zračnosti - Guclu, Rahmi (Strojniški vestnik, 2004)
In this paper a four-degrees-of-freedom vehicle model is used in order to design and check the performance of fuzzy-logic-controlled (FLC) active suspensions without causing any degeneration in the suspensions' working limits. Aiming at a zero displacement for a sprung mass might finish the suspensionsć working distance. Therefore, in this paper a new approach is proposed. The force actuators are mounted parallel to the suspensions. The main idea behind proposing a fuzzy-logic controller is its success, the ability to use these types of controllers on vehicle systems and the ability to overcome the suspension-gap degeneration problem within the fuzzy-control algorithm. The improvement in the ride comfort is achieved by decreasing the amplitudes of the motions of the vehicle body. The body bounce and the pitch motions of the vehicle are simulated in both the time domain, in the case of travelling over a ramp-step road profile, and in the frequency domain. The simulation results are compared with the results from passive suspensions. At the end of the paper , the performance of the controller, the advantage of theproposed approach and the improvement in the system performance are discussed in terms of the ride comfort.
Keywords: modeli vozil; obese; logično mehki krmilniki; simuliranje; vzmetenje; vozila; krmiljenje; mehka logika; simulacije